Improved performances of polyacrylamide gel by addition of a new type of polymer : detection of allelic losses - Korolija, Marina (Array, 2008)
Abstract: The aim of this study was to improve detection of heterozygous samples and loss of heterozygosity using a new type of gel polymer. A total of 60 samples of normal and tumor colon tissue were tested. Elctrophoresis of amplified loci was performed on a standard acrylamide / N,Nmethylenebisacrylamide gel, and the same gel containing Spreadex polymer, NAB (native acrylamide- bis). Standard gel displayed 36 samples of normal tissue as homozygous. Electrophoresis of the same samples on gel with addition of polymer revealed 12/36 heterozygous samples. Five of 12 matched tumor samples displayed loss of heterozygosity that could not be detected on standard gel, because of its lower resolving power. Electrophoresis on a new polymer presents a simple, inexpensive, reproducible and non-radioactive method for loss of heterozygosity detection, with improved performances such as increased sensitivity, decreased amount of a sample and improved separation of closely spaced bands. Application of the polymer may contribute to a vide variety of diagnostic procedures